When Shopping Becomes Urgent: Discursive Power and Ethical Tensions in Indonesian Beauty Live Streaming Commerce - Putri, Tiara Rahmadani; Riani, Yuyun Agus; Oktaviani , Fitri Hariana (Graduate School Universitas Brawijaya, 2026)
Objective: Live-streaming commerce has become a dominant promotional practice in Indonesia’s beauty industry, enabling real-time interaction among brands, hosts, and consumers. While framed as transparent and engaging, this format raises ethical concerns related to digital persuasion. This study critically examines how ethically problematic communication practices are discursively constructed and normalized in Indonesian beauty live streaming. Design/Methods/Approach: Adopting a qualitative, critical approach, this analysis examines eight live-streaming sessions on TikTok Live and Shopee Live using Fairclough’s three-dimensional Critical Discourse Analysis (CDA), enhanced by Foucault’s concept of governmentality. Findings: The analysis reveals that false urgency, false scarcity, false advertising, and emotional manipulation are systematically produced through linguistic cues, visual intensification, and affective interaction. These practices are reinforced by parasocial communication, selective audience engagement, and repetitive promotional performances, which legitimize market-driven persuasion and constrain critical reflection. Originality/Value: Socially, these communicative strategies reflect neoliberal market logic, framing consumption as a moralized, time-sensitive obligation, thereby normalizing digital consumerism. Practical/Policy implication: This study contributes by integrating CDA with governmentality to show how ethical violations in live streaming are not isolated marketing tactics, but normalized practices embedded within platform-driven market structures. Keywords: Live streaming commerce; ethical communication, critical discourse analysis, digital persuasion; neoliberalism JEL Classification: M31; L81; Z13